Analisis Strategi Komunikasi dan Lingkungan Kerja dalam Meningkatkan Kinerja Karyawan Cipta Grafika - Putri Sakina Al Haerani; Aji Tuhagana; Zenita Apriani (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to understand and analyze the results of communication strategy and work environment analysis in improving employee performance at Cipta Grafika Karawang. The location of this research is at Cipta Grafika Karawang. The research method employs a qualitative descriptive approach, expressed through careful word selection, sentence composition, detailed narration, and visual representation. Data collection techniques involve interviews, observations, and documentation. The research findings indicate that communication, comprising downward communication, upward communication, horizontal communication, and interline communication at Cipta Grafika, are well-established and efficient. The work environment is also reported to be good and comfortable. Effective communication and a comfortable working environment contribute to enhancing employee performance. It is essential to continuously maintain good communication and a comfortable work environment to sustain and further improve employee performance at Cipta Grafika.